A blue ribbon romance eaudiobook - Nascosta, C.M (Tantor Media, 2023)
Morning Glory Milking Farm was just another quick tug—machine operated facility, no different from all the rest. Sure, they had big pharma money and special hands-on amenities the other milking joints couldn't boast, but at the end of the day it was the same old story—cash he didn't actually need in the bank, all for doing what he would have done for free anyway. Get in, get out, get on with his day. At least, that's what he thought. Rourke doesn't know why he's so drawn to a particular milking tech . . . he doesn't know anything about her, after all. Not what she looks like without a mask concealing her face, not even her name. He only knows he can't stay away. He wasn't looking for love, but it managed to find him in most unlikely of places, and now he's determined to prove that you can teach an old bull new tricks. Fall in love all over again with Violet & Rourke's romance . . . from the other side of the milking table. Contains mature themes.